2006
DOI: 10.1109/tap.2006.882195
|View full text |Cite
|
Sign up to set email alerts
|

Polar Integration for Exact Space-Time Quadrature in Time-Domain Integral Equations

Abstract: A space-time polar quadrature technique for numerical integration of Green's function interactions in time-domain integral equations is presented. The method transforms 2-D surface space-time integrals associated with vector and scalar potentials to a 1-D integral that is performed using Gauss-Legendre integration. The advantage of the presented technique compared to standard 2-D Gaussian quadrature is that time delays between each section of the source basis function and the observation point are accounted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Similarly, the scalar potential can be written as (4) where denotes the integration with respect to time. In (3) and (4), are chosen as the SWG functions.…”
Section: Evaluation Of the Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the scalar potential can be written as (4) where denotes the integration with respect to time. In (3) and (4), are chosen as the SWG functions.…”
Section: Evaluation Of the Potentialsmentioning
confidence: 99%
“…Recently, closed-form expressions of the retarded-time potentials and fields were developed via Radon transform (RT) interpretation of potential integrals that appear in the surface integral equations (SIEs) [2], [3]. Other exact integration approaches for SIEs have also been suggested [4], [5]. Later, it was shown that by using the closed-form expressions, more accurate results were obtained in the solutions of SIEs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the inclusion of additional uncoupled filtering circuit elements is relatively inexpensive in comparison to the computationally more demanding coupled circuit elements. As an alternative approach to our filtering approach, the geometrical arrangements of the delay distances is used in [11] to improve the phase response for very high frequencies.…”
Section: High Frequency Filteringmentioning
confidence: 99%
“…Later, implicit time stepping algorithms and appropriate smooth temporal basis functions are also proposed to overcome the above mentioned drawbacks [5][6][7][8][9][10]. Recent studies show that accuracy computation of the MOT impedance matrix is considered as a cure factor, effecting the late time stability and accuracy of the MOT solver [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%